1986
DOI: 10.1002/etc.5620050209
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of single‐species, microcosm and experimental pond responses to atrazine exposure

Abstract: Results from single‐species toxicity tests form the basis for guidance about concentrations of chemicals that are likely to be environmentally hazardous. Microcosm bioassays have been proposed as better tools for this purpose under some circumstances. Rarely have comparisons been made among the responses in the various test systems and those seen in natural communities. We compared the responses among single‐species algal assays, a synthetic microcosm (the Taub microcosm) and experimental ponds exposed to simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 20 publications
3
34
1
1
Order By: Relevance
“…For the herbicide atrazine, Larsen et al (1986) recently compared the sensitivity of different systems. They constructed dose-response curves and estimated the EC 50 values in single-species tests, generic microcosms and experimental ponds.…”
Section: Introductionmentioning
confidence: 99%
“…For the herbicide atrazine, Larsen et al (1986) recently compared the sensitivity of different systems. They constructed dose-response curves and estimated the EC 50 values in single-species tests, generic microcosms and experimental ponds.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have generally concluded that significant effects on primary producers typically only begin to occur with prolonged atrazine concentrations N30 μg/L and that subsequent to any disturbances algal populations recover (Gruessner and Watzin, 1996;Nyström et al, 2000;Baxter et al, 2011;Huber, 1993;Solomon et al, 1996;Giddings, 2012). However, mesocosm studies testing atrazine concentrations N 50 μg/L for extended periods have shown decreased activity, abundance, or diversity, or shifts in algal community structure (Kosinski and Merkle, 1984;Hamala and Kollig, 1985;Larsen et al, 1986;Krieger et al, 1988;Hamilton et al, 1988;Hamilton and Mitchell, 1997;Nyström et al, 2000;Guasch et al, 2007).…”
mentioning
confidence: 98%
“…Much research has been conducted using freshwater pond (lentic) micro-or mesocosms (e.g., Larsen et al, 1986;Hoagland et al, 1993;Berard et al, 1999),flowing (lotic) mesocosms (e.g., Lynch et al, 1985;Gruessner and Watzin, 1996;Nyström et al, 2000;Muñoz et al, 2001), or on natural lotic communities (Jurgensen and Hoagland, 1990;Lakshminarayana et al, 1992;Guasch et al, 1998;Dorigo et al, 2004;Laviale et al, 2011). However, to our knowledge, this initiative is the only such study to examine in situ the effects of atrazine on periphyton and phytoplankton dynamically throughout the growing season in several Midwestern agricultural stream areas where atrazine use is among the highest (Solomon et al, 1996;Andrus et al, 2013).…”
mentioning
confidence: 99%
“…However, statistical approaches, such as structural equation models, or additional experiments are often necessary to determine whether the observed effects of the contaminant are direct or indirect (mediated by species interactions) (Halstead et al 2014, McMahon et al 2012, Rohr, Schotthoefer, et al 2008, Schotthoefer et al 2011). Effects of contaminants on species interactions in outdoor mesocosms studies have also been shown to match effects of contaminants in natural systems (Larsen et al 1986, Niederlehner et al 1990, Pontasch and Cairns 1991, Pontasch et al 1989, Rohr, Schotthoefer, et al 2008, Stay et al 1989, Taub 1997b), demonstrating that outdoor mesocosm studies can capture the complexities of natural systems without sacrificing the ability to assess causal relationships. Studies of species interactions in the laboratory, of course, are less likely to capture the realities of communities in the wild and correlational studies at the community level cannot determine causality.…”
Section: Community Levelmentioning
confidence: 95%
“…Although there are some experimental ponds where chemicals have been applied and effects quantified (Boone et al 2004, Fairchild and Sappington 2002, Hanazato 1998, Larsen et al 1986), generally it is challenging to get approvals to apply chemicals to entire natural ecosystems and thus most effects on natural ecosystems tend to be correlational with a relatively low level of confidence in assessing cause-effect relationships. Hence, many ecosystem-level studies are natural experiments or correlational because they are conducted in nature.…”
Section: Ecosystem Levelmentioning
confidence: 99%